Stress exposure in intrauterine life is associated with shorter telomere length in young adulthood - Entringer, Sonja (National Academy of Sciences, 2011)
Leukocyte telomere length (LTL) is a predictor of age-related disease onset and mortality. The association in adults of psychosocial stress or stress biomarkers with LTL suggests telomere biology may represent a possible underlying mechanism linking stress and health outcomes. It is, however, unknown whether stress exposure in intrauterine life can produce variations in LTL, thereby potentially setting up a long-term trajectory for disease susceptibility. We, therefore, as a first step, tested the hypothesis that stress exposure during intrauterine life is associated with shorter telomeres in adult life after accounting for the effects of other factors on LTL. LTL was assessed in 94 healthy young adults. Forty-five subjects were offspring of mothers who had experienced a severe stressor in the index pregnancy (prenatal stress group; PSG), and 49 subjects were offspring of mothers who had a healthy, uneventful index pregnancy (comparison group; CG). Prenatal stress exposure was a significant predictor of subsequent adult telomere length in the offspring (178-bp difference between prenatal stress and CG; d = 0.41 SD units; P < 0.05). The effect was substantially unchanged after adjusting for potential confounders (subject characteristics, birth weight percentile, and early-life and concurrent stress level), and was more pronounced in women (295-bp difference; d = 0.68 SD units; P < 0.01). To the best of our knowledge, this study provides the first evidence in humans of an association between prenatal stress exposure and subsequent shorter telomere length. This observation may help shed light on an important biological pathway underlying the developmental origins of adult health and disease risk.